Institucionalización del aprendizaje servicio en la Facultad de Ciencias Empresariales de la Universidad del Bío-Bío: vinculando la educación superior con la comunidad local (2020)
The service-learning methodology offers countless opportunities for higher education to strengthen the teaching-learning process through the connection between students and the community. Service-learning allows extending the reference areas of the teaching work, from the classroom to the fieldwork. Thus, students can recognize the particularities of the environment and discover the needs of the local community. The aim of this study describes the actions developed to integrate and institutionalize the service-learning methodology as part of the development of its undergraduate courses in the Faculty of Business Sciences at the University of Bío-Bío of Chile. Results indicate that to date, 901 students and 19 teachers have participated, working collaboratively with community partners in training sessions and specific consultancies. Currently, 276 community partners belonging to 20 institutions in the regions of Biobío and Ñuble, Chile, have received assistance and, most of them show a high level of satisfaction with the actions developed. This methodology provides students with technical skill, value, and attitude development opportunities. Furthermore, it allows students to achieve greater commitment and contribution to the territorial development of the regions in which they study.